Sustainable forest management for small farmers in Acre state in the Brazillian Amazon. - OLIVEIRA, M. V. N. d'. (2000)
Tese (Doctor of Philosophy) - Department of Plant & Soil Science, University of Aberdeen, Scothland. Supervisors: M. d. Swaine; David F. R. P. Burslem.